Biosynthetic considerations of triscatechol siderophores framed on serine and threonine macrolactone scaffolds. Issue 7 (8th June 2017) - Reitz, Zachary L.; Sandy, Moriah; Butler, Alison
Abstract : The biosyntheses of a family of enterobactin variants – amino acid substitution, insertion, and derivatization, and macrolactone expansion – is reviewed. Abstract : Bacteria often produce siderophores to facilitate iron uptake. One of the most studied siderophores is enterobactin, the macrolactone trimer of 2, 3-dihydroxybenzoyl-l -serine, produced by E. coli and many other enteric bacteria. Other siderophores are variants of enterobactin, with structural modifications including expansion of the tri-serine core to a tetra-serine macrolactone, substitution ofl -serine withl -threonine, insertion of amino acids ( i.e., Gly, l -Ala, d -Lys, d - andl -Arg, l -Orn), catechol glucosylation, and linearization of the tri-serine macrolactone core. In this review we summarize the current understanding of the biosyntheses of these enterobactin variants, placing them in contrast with the well-established biosynthesis of enterobactin.